The Effect of the Phonics Method Using Beginning Reading Media on Primary School Students' Beginning Reading Skills - Ayuningtyas, Tyagita; Iswara, Prana Dwija; Sopandi, Wahyu; Sujana, Atep (Universitas Pendidikan Indonesia, 2025)
One significant obstacle to improving basic literacy standards in Indonesia is the low initial reading proficiency among primary school students. To strengthen students' understanding of letter-sound relationships, innovative teaching approaches are essential. This study investigated the combined effects of phonics instruction and Beginning Reading (BR) media on elementary students' early reading abilities. Using a quasi-experimental pre-experimental design, the research employed descriptive and inferential statistical analysis of data collected through questionnaires, interviews, and a one-group pretest-posttest framework. Eighteen participants demonstrated pretest scores ranging from 28.46 to 70.76, reflecting varying baseline reading levels. Following the instructional intervention, posttest results revealed substantial improvement, with scores climbing to 82-100 and an average N-Gain score of 82.85. These outcomes demonstrate marked progress in reading competency, providing robust empirical support for integrating phonics methodology with interactive BR media. The results highlight two key findings: (1) the effectiveness of combining systematic phonics with multimedia tools, and (2) technology's role in creating engaging, practical learning solutions for foundational literacy. This research contributes meaningfully to primary education by validating an evidence-based approach that addresses Indonesia's literacy challenges while aligning with contemporary digital learning environments. The demonstrated improvements in reading skills underscore the potential of this combined methodology to transform early reading instruction.